AN OBSERVATIONAL STUDY ON ASSOCIATION OF OCULAR MORBIDITIES WITH BODY MASS INDEX IN CHILDREN - Harshita, P.H.N.S.S; Sahu, Pallavi Priyadarsani; Padhee, Sourav; Mohanty, Soumya Kanta; Pokarana, Ridhima; Sadhwan, Parul (Student's Journal of Health Research Africa, 2023)
Background: It is important to determine the effects of obesity and hypertension on the eyes so that they might be utilized as prognostic indicators. In children and adolescents who are overweight and/or have SAH, this paper intended to evaluate the prevalence of ophthalmological changes. Methods: This hospital-based Cross-sectional observational study was conducted on paediatric patients presenting to the outpatient department of ophthalmology at Pradyumna Bal Memorial Hospital, which is affiliated with Kalinga Institute of Medical Sciences, KIIT University, located in Bhubaneswar, Odisha, India. The procedure was executed between September of 2020 and September of 2022. The sample population of this study included 500 patients. The institutional ethical committee approved the study. Results: In our survey, there were marginally more girls than men. Within the age groupings (groups a, b, and c) and the plethora of diseases specific to each group, there was statistical significance. Half of the participants in our study are underweight, whereas a smaller percentage are fat. According to our study, socioeconomic status is a key factor in visual morbidities. Lower middle class makes up the majority of the kids. Conclusion: Obesity and SAH have links to changes in the ophthalmology, particularly in the retinal vascular diameter. A quantitative evaluation is not possible due to a lack of standardization.